FEATURES OF THE DEVELOPMENT OF CIRCULAR BUSINESS MODELS IN THE CONDITIONS OF SUSTAINABLE DEVELOPMENT - Заблоцька, Ріта Олександрівна; Русак, Денис Миколайович (Journal of Strategic Economic Research, 2024)
The presented work reflects the current issue of economic science today, which concerns the development of circular business models. Thus, circular business models have become an important tool for achieving the goals of sustainable development. They are based on the concept of the "circular economy", which differs from the traditional linear economy in that it strives to reduce waste, maximize the reprocessing of resources and minimize the negative impact on the environment. The purpose of the work is to determine the peculiarities of the development of circular business models in the conditions of sustainable development and to analyze their quality. The methods of the current research are defined as: analysis method, synthesis method, deduction and induction methods, logical method, comparative method, tabular method, graphic method for graphically displaying some research elements. The main findings of the study are: circular business models involve the use of resources based on the principles of waste reduction, reuse, repair, modernization and recycling, and they encourage businesses to consider the life cycle of products and services, in particular their disposal and opportunities for reuse of materials. As part of circular business models, companies often adopt new technologies and processes, which may include the development of new materials, as well as the development of products that have a longer life or the ability to be reused. Circular business models focus on changing relations between enterprises and consumers. Such models can bring economic benefits, such as reducing raw material costs, reducing waste management costs, and creating new revenue streams through maintenance and repair models. This is achieved by reducing the amount of waste, reducing the use of natural resources and reducing emissions of pollutants. This approach helps to improve the ecological balance and contributes to the preservation of biodiversity. The development of circular business models in conditions of sustainable development is an important aspect of the transition to a more environmentally responsible and economically profitable economy. They contribute to reduced environmental impact, economic growth through innovation and provide new business opportunities.